Análise da relação entre o comprometimento e a aprendizagem organizacional: um estudo em uma organização hospitalar - Santos, Débora Luíza dos (2009)
Considering the learning relevance and organizational commitment (CO) for the success of contemporary organizations, especially hospital organizations, highlighted as major complex organizations (CORREIA, MATOS and LINS, 2007), this study looked for a better understanding of the relationship between commitment and organizational learning (AO) in a hospital organization from their collaborators‟ perspective. To reach the overall goal, the following specific goals have been identified: to analyze the present components of the CO in the study; verify AO enabling and difficult factors in the organization, identify the AO predominant level in context, and link the enable factors to learning levels, the CO components in the organization under study. The descriptive nature and the quantitative / qualitative approach research had as a methodological strategy the case study, applied to a medium to large hospital organization, located in the center of the state of Rio Grande do Sul. First of all, the study subjects were 148 employees from nursing sectors, administrative and support sectors, defined according to the random probability sampling technique, which two questionnaires were applied, the Organizational Learning Scale of Goh and Richard (1997), validated in Brazil by Angelim and Guimarães (2003), and Meyer‟s instrument, Allen and Smith (1993), validated in Brazil by Medeiros and Enders (1998). Second, ten hospital managers participated of the study which involved semi-structured interviews whose script was based on the literature about AO levels and commitment theoretical frameworks. The data were tabulated and analyzed in a quantitative way with the aid of SPSS 13.0 supporting software and Excel, to perform simple statistical techniques and multivariate analysis and the interviews were qualitatively analyzed using the content analysis. There was a predominance of affiliates and affective components in the organization, which indicates a strong emotional connection and an integration of the respondents to the organization. The study also contributed to reinforce the multiple components of CO researches, corroborating an existence of a fourth component, the affiliate component, discovered in the study by Medeiros et al. (1999). Similarly, in the AO field, the research reinforced the OLS applicability in Brazilian culture, identifying three new categories of factors and management practices of AO enabling: Stimulation of team work and experimentation , AO committed leadership , and Integration of the sectors and organizational mission dissemination . In a general way it was noticed that favorable aspects to the opening through the encouragement of innovative processes in the sectors coexist with elements such as the central decisions, the difficulty of integration between sectors and the little recognition of the management importance in the AO promotion in the organization under study, which are reflected in the predominance of a single loop level of learning. It was also identified that the more committed the employees are, the greater the perception of factors and management practices conducive to learning and therefore the greater the chances the scenarios promote the AO.